Identification of the critical therapeutic entity in secreted Hsp90α that promotes wound healing in newly re-standardized healthy and diabetic pig models. - Kathryn O'Brien; Ayesha Bhatia; Fred Tsen; Mei Chen; Alex K Wong; David T Woodley; Wei Li (PLoS ONE, 2014)
Chronic and non-healing skin wounds represent a significant clinical, economic and social problem worldwide. Currently, there are few effective treatments. Lack of well-defined animal models to investigate wound healing mechanisms and furthermore to identify new and more effective therapeutic agents still remains a major challenge. Pig skin wound healing is close to humans. However, standardized pig wound healing models with demonstrated validity for testing new wound healing candidates are unavailable. Here we report a systematic evaluation and establishment of both acute and diabetic wound healing models in pigs, including wound-creating pattern for drug treatment versus control, measurements of diabetic parameters and the time for detecting delayed wound healing. We find that treatment and control wounds should be on the opposite and corresponding sides of a pig. We demonstrate a strong correlation between duration of diabetic conditions and the length of delay in wound closure. Using these new models, we narrow down the minimum therapeutic entity of secreted Hsp90α to a 27-amino acid peptide, called fragment-8 (F-8). In addition, results of histochemistry and immunohistochemistry analyses reveal more organized epidermis and dermis in Hsp90α-healed wounds than the control. Finally, Hsp90α uses a similar signaling mechanism to promote migration of isolated pig and human keratinocytes and dermal fibroblasts. This is the first report that shows standardized pig models for acute and diabetic wound healing studies and proves its usefulness with both an approved drug and a new therapeutic agent.